Lírica e sociedade : um olhar sobre a Obra Poética de Manuel da Fonseca - Bergamasco, Rosilda de Moraes (2012)
Manuel da Fonseca is considered one of the greatest writers of the Portuguese Neorealism, and has distinguished himself as a poet, storywriter and novelist. But his engagement with the political and social issues of his country goes beyond a mere doctrinal adherence to neorealism movement, making his literature to evidence an ethic and aesthetic whose essence is translated into a deep involvement with the human being. However, the studies about the neorealism poetry and specifically the poetic production of Manuel da Fonseca are scarce, justifying then the present research, which aims to contribute both in researches on the poetry of a writer who, as few, knew how to honor the Neorealism, the language and the Portuguese literature, as to expand the researches on the neorealism poetry. Considering this, the objective of this paper is to discuss issues relating to lyrical poetry and to the studies on the Portuguese Neorealism. Through the analysis of poems contained in "Obra Poética", from the Portuguese writer Manuel da Fonseca, it seeks to examine the discursive strategies used by the poet in order to establish an area of social criticism. In order to emphasize these strategies, it seeks to show that the image of the Portuguese region of Alentejo is central in the lyrical poetry of Manuel da Fonseca. To do so, this research will use theoretical concepts as Cara, Jakobson, Moisés, D'Onofrio, Benjamin and Staiger related to lyrical poetry and its characteristics, as well as shall adopt the position of certain theorists like Adorno, Gullar, Eliot and the Mukarovsky in order to establish the possible relations between lyrical poetry and society. We will take into consideration, as well, the concepts that are part of the neorealism aesthetic and its historical and cultural context, under the theoretical assumptions of Torres, Birmingham, Lourenço and Reis.